A Bayesian approach of Greek strike activity. (9th September 2009) - Sfakianakis, Michael E.
This work deals with a Bayesian approach of Greek strike activity concerning all the sectors ordered by the respective code numbers given by the National Statistical Service of Greece (hereafter NSSG). Sfakianakis and Hourmentis (2003) specified and estimated conventional strike equations by applying stepwise multiple regression analysis, using the data for all strikes based on the data collected by NSSG, and compared the effects of the explanatory variables. The results are presented due to the comparison of Bayesian estimates (using BUGS) with the respective classical MLE estimates (using SPSS). The Bayesian approach confirms the selected models due to the multiple regression procedure. It confirms also the similarities and the specificities of Greek strike activity in comparison with the respective ones regarding other countries.